2010
DOI: 10.1038/nsmb.1910
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the cholera toxin secretion channel in its closed state

Abstract: The type II secretion system (T2SS) is a macromolecular complex spanning the inner and outer membranes of Gram-negative bacteria. Remarkably, the T2SS secretes folded proteins including multimeric assemblies like cholera toxin and heat-labile enterotoxin from Vibrio cholerae and enterotoxigenic Escherichia coli, respectively. The major outer membrane T2SS protein is the “secretin” GspD. Electron cryomicroscopy reconstruction of the V. cholerae secretin at 19 Å resolution reveals a dodecameric structure reminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
199
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(213 citation statements)
references
References 59 publications
13
199
1
Order By: Relevance
“…While flagella include a P-ring spanning the peptidoglycan layer and an L-ring transversing the OM, injectisomes contain a secretin-type ring, probably acquired from various sources later in evolution [38], that spans both of these layers. The reason for this divergence is unclear; however, the flagellar P-and L-rings need to function as bushings for the rotating flagellum, whereas secretins are very stable structures, shown to seal the OM until their conformation is changed to an open state [39,40], possibly by the growing needle.…”
Section: Structural and Functional Homologies Among The T3ss And Othementioning
confidence: 99%
“…While flagella include a P-ring spanning the peptidoglycan layer and an L-ring transversing the OM, injectisomes contain a secretin-type ring, probably acquired from various sources later in evolution [38], that spans both of these layers. The reason for this divergence is unclear; however, the flagellar P-and L-rings need to function as bushings for the rotating flagellum, whereas secretins are very stable structures, shown to seal the OM until their conformation is changed to an open state [39,40], possibly by the growing needle.…”
Section: Structural and Functional Homologies Among The T3ss And Othementioning
confidence: 99%
“…Here it is suggested that the exotoxin sitting on the grown pseudopilus induces conformational changes in the secretin, which results in the opening of the periplasmic gate and the final release of the toxin (37,57). If a pseudopilus triggers opening of the Thermus PilQ complex, thereby enabling DNA uptake, a direct interaction of the pseudopilus structures and the PilQ complex is a prerequisite.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
“…35 It is highly conserved and predicted to contain several -strands 36 embedded in the outer membrane to form the actual pore through which transport occurs. 21 The N-terminal periplasmic region displays conservation only in secretins from related secretion pathways 29 and may be involved in substrate recognition, 28,37 gating of the proposed channel 35,38 and DNA binding 39 as well as contributing to subunit oligomerization. 35,40 The atomic structures of periplasmic fragments from two secretins, EscC from enteropathogenic E. coli and GspD from enterotoxigenic E. coli, have previously been determined.…”
Section: (31)mentioning
confidence: 99%
“…17,19 Secretins are large homo-oligomeric assemblies built up of 50-70 kDa subunits, with 12-14 subunits forming a ring structure of approximately 100-150 Å in diameter. 20,21,22,23,24,25,26,27,28 They comprise a superfamily 29,30 and form components of several distinct secretion systems in the outer membrane, including the type-two secretion system (TIISS), 31,32 type-three secretion system (TIIISS) 26 and Type-IV pilus biogenesis system. 30,33,34 All secretins consist of two major regions.…”
Section: (31)mentioning
confidence: 99%